Human factors in anaesthesia: a narrative review. (11th January 2023) - Kelly, F. E.; Frerk, C.; Bailey, C. R.; Cook, T. M.; Ferguson, K.; Flin, R.; Fong, K.; Groom, P.; John, C.; Lang, A. R.; Meek, T.; Miller, K. L.; et al.
Summary: Healthcare relies on high levels of human performance, as described by the 'human as the hero' concept. However, human performance varies and is recognised to fall in high‐pressure situations, meaning that it is not a reliable method of ensuring safety. Other safety‐critical industries embed human factors principles into all aspects of their organisations to improve safety and reduce reliance on exceptional human performance; there is potential to do the same in anaesthesia. Human factors is a broad‐based scientific discipline which aims to make it as easy as possible for workers to do things correctly. The human factors strategies most likely to be effective are those which 'design out' the chance of an error or adverse event occurring. When errors or adverse events do happen, barriers are in place to trap them and reduce the risk of progression to patient and/or worker harm. If errors or adverse events are not trapped by these barriers, mitigations are in place to minimise the consequences. Non‐technical skills form an important part of human factors barriers and mitigation strategies and include: situation awareness; decision‐making; task management; and team working. Human factors principles are not a substitute for proper investment and appropriate staffing levels. Although applying human factors science has the potential to save money in the long term, its proper implementation may require investment before reward can be reaped. This narrative review describes what is known about human factors in anaesthesia to date.